Reflections on Jørgen Jensen: The Prehistory of Denmark: from the Stone Age to the Vikings – Gyldendal, Copenhagen, 2013 - Høiris, Ole (Danish Journal of Archaeology, 2015)
In the Danish version, Jørgen Jensen’s Prehistory of Denmark is presented as the continuation of an archaeological tradition going back to 1843. Jensen’s work is the fourth, and what is common to these archaeological descriptions of our past is that they discuss our Danish origin and identity, related to the worldview of Romanticism, and reflect the most important issues at the time of their publication. The background is that Denmark was reduced to a very small state during this period, that Danes migrated to the area after the Ice Age, and that we have lived on the periphery of cultural evolution and civilisation. By presenting his predecessors’ reflections on such issues, I analyse aspects of Jensen’s work from this perspective.